2020
DOI: 10.1101/2020.04.20.052175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Searching through functional space reveals distributed visual, auditory, and semantic coding in the human brain

Abstract: The extent to which brain functions are localized or distributed is a foundational question in neuroscience. In the human brain, common fMRI methods such as cluster correction, atlas parcellation, and anatomical searchlight are biased by design toward finding localized representations. Here we introduce the functional searchlight approach as an alternative to anatomical searchlight analysis, the most commonly used exploratory multivariate fMRI technique. Functional searchlight removes any anatomical bias by gr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…By focusing on speech representations, the present study provides four empirical contributions to the investigation of auditory representations in brains and deep learning models (Yamins & DiCarlo, 2016;Keshishian et al, 2020;Berezutskaya et al, 2020;Khosla et al, 2020;Kell et al, 2018;Kumar et al, 2020;Koumura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By focusing on speech representations, the present study provides four empirical contributions to the investigation of auditory representations in brains and deep learning models (Yamins & DiCarlo, 2016;Keshishian et al, 2020;Berezutskaya et al, 2020;Khosla et al, 2020;Kell et al, 2018;Kumar et al, 2020;Koumura et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…speech-to-text using Dutch, English or Bengali). Previous studies have already shown that deep convolutional neural networks trained to classify words, musical genres (Kell et al, 2018;Kumar et al, 2020) or natural sounds (Koumura et al, 2019), generate brain-like representations, in the sense that one can find a linear correspondence between the activation of the neural networks and the activations of the brain (Figure 1). This similarity can be quantified with a "brain score" (Yamins et al, 2014), a correlation between the brain measurements and a linear projection of the model's activations, under the assumption that representations are defined as linearly exploitable information (Hung et al, 2005;Kamitani & Tong, 2005;Kriegeskorte & Kievit, 2013;King et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…We previously validated that this fitting procedure produces accurate simulations of real data [23]. We have used fmrisim to evaluate the power of different experimental design parameters [23], and also to evaluate the efficacy of new analysis methods [78,79].…”
Section: The Solutionmentioning
confidence: 99%
“…SRMs 'learn' a mapping of multiple subjects into the same space, enabling the detection of group differences, or the study of relations between brain activity and movie annotations, for example [54]. Recently, SRM was used to map voxel activity into a functional space (as opposed to an anatomical one), to study the brain representation of, among others, visual and auditory information while receiving naturalistic audiovisual stimuli [29]. Nonetheless, while SRM is one of the most powerful techniques for extracting cognitively-relevant signals from fMRI data, there is still room for improvement.…”
Section: Related Workmentioning
confidence: 99%